STRATEGIC ANALYSIS OF BALI TUNA EXPORT TRANSPORTATION LOGISTICS PATTERNS IN THE FACING OF THE COVID-19 PANDEMIC EMERGENCY SITUATION: ANALYTICAL HIERARCHY PROCESS (AHP) APPROACH - Sitanggang, Charles Paulinus Marulitua; Taryono; Santoso, Joko (Departemen PSP IPB, 2025)
The COVID-19 pandemic caused major disruptions to the tuna export logistics chain from Bali, primarily due to air transport restrictions, limited logistics infrastructure, and fluctuating production volumes. This study aims to evaluate the most optimal export transportation logistics strategy in emergency situations using the Analytical Hierarchy Process (AHP). The decision hierarchy includes four main criteria—logistics cost, reliability, resilience, and delivery time—and four strategic alternatives: air freight optimization, sea freight support, development of integrated logistics centers, and land-sea multimodal transport. The results show that delivery time (0.34945) and reliability (0.33064) are the dominant factors. Air freight optimization emerged as the best strategy (ideal score: 1.000), ensuring rapid distribution and cold chain integrity. This study highlights the importance of resilient logistics by emphasizing speed, reliability, and adaptability in response to external shocks. The findings provide strategic insights for stakeholders in formulating robust fisheries export logistics policies to anticipate future global disruptions. Key words: cold chain, freight consolidation, logistic efficiency, resilience, transport modes